Low‐dose liquid cell electron microscopy investigation of the complex etching mechanism of rod‐shaped silica colloids - Sina Sadighikia; Albert Grau‐Carbonell; Tom A.J. Welling; Ramakrishna Kotni; Fabian Hagemans; Arnout Imhof; Marijn A. van Huis; Alfons van Blaaderen (Nano Select, 2021)
Abstract Understanding the chemical structure of rod‐shaped silica colloidal particles is attainable by investigating their etching mechanism in solution. Liquid Cell (Scanning) Transmission Electron Microscopy (LC‐(S)TEM) is a promising technique through which the etching of these particles can be observed in real time, and at the single particle level, without possible deformations induced by the surface tension of dried particles. However, the presence of high energy electrons, and the different geometry in LC experiments may alter the conditions of in situ experiments compared to their ex situ counterparts. Here we present a controlled low‐dose LC‐STEM study of the basic etching process of micron‐sized silica rods that are immobilized on the SiN window of a liquid cell. The results show that using low‐dose imaging conditions, combined with a low accumulated electron dose, and optimized flow rates of solutions allow for investigation of the chemical etching mechanism of silica colloidal particles using the LC‐(S)TEM technique with negligible effects of the electron beam. A comparison of ex situ etching experiments with LC‐STEM observations show that the LC geometry can play a crucial role in LC‐STEM experiments where the diffusion of the etching particles is important, which should be considered during the interpretations of LC‐STEM results.